Tales of Tangier The Complete Short Stories of Mohamed Choukri - Choukri, Mohamed (The Margellos World Republic of Letters, 2023)
The complete short stories of acclaimed Moroccan author Mohamed Choukri, translated into English and collected in one volume for the first time Mohamed Choukri's vivid stories invite the reader to wander the streets of Tangier, the ancient coastal crossroads between Europe and Africa, and to meet its denizens at markets, beaches, cafés, and brothels. Choukri's Tangier is a place where newborns are for sale, swindlers hawk the Prophet's shoes, and boys collect trash to sell for food. Choukri says that "writing is a protest, not a parade." And in these thirty-one stories he privileges the voices of those ignored by society: the abused, the abandoned, the addicted. The tales are at once vibrant local vignettes and profound reflections on the lives, sufferings, and hopes of Choukri's fellow Tangerines